Gender Discourse in the Perspective of Comte and Durkheim's Structuralism - Cristophel Van Harling (Indonesian Center for Religion and Society Studies (InTReSt), 2026)
This study aims to analyze how social structures influence gender roles based on the structuralist perspective through the thoughts of Auguste Comte and Emile Durkheim. The study applies a qualitative descriptive method with a literature study approach, analyzing academic texts to identify the construction of gender roles through cultural norms and social institutions. Comte's three stages of societal evolution (theological, metaphysical, and positive) highlight the dynamic nature of gender roles shaped by dominant epistemologies. Meanwhile, Durkheim's theory of mechanical and organic solidarity frames the gender role transition from rigid traditional assignments to more flexible roles in modern society. The results show that although structural changes have occurred, gender inequality persists due to lingering patriarchal norms. Therefore, gender equity requires systemic reforms in policies and socio-cultural structures. Understanding the underlying structure of society helps to reframe gender roles toward a more egalitarian social order.